Systematic Review: Metode Pembelajaran dalam Materi Ilmu Tajwid Al-Qur’an Hadits Siswa Madrasah Tsanawiyah di Indonesia - Hasanah, Nurul; Nur Habibi, Muhammad (UIR Press, 2024)
Learning methods are part of pedagogical competence that must be explored continuously, so there is a need for literature specifically developed to examine how these learning methods have been applied in previous research. This research aims to explore what kind of learning methods teachers use in recitation science material in Al-Qur'an Hadith subjects among Islamic boarding school students in Indonesia from 2014 to 2024. The research design used is a systematic review using the Preferred Reporting Items method for Systematic Review and Meta-Analysis (PRISMA), which will select articles collected through the Identification, Screening, Eligibility, and Included stages. Based on the results of exploration through this article, it was found that there are three learning methods used in Tajwid science material, namely Index Card Match, Peer Tutor, and Contextual Teaching Learning.